A flow‐through column electrolytic cell for supercritical fluid chromatography*. Issue 20 (12th September 2017) - Yamamoto, Kazuhiro; Ueki, Tatsuya; Higuchi, Naoyuki; Takahashi, Kouji; Kotani, Akira; Hakamata, Hideki
Abstract: A novel flow‐through column electrolytic cell was proposed as a detector to obtain current signals for supercritical fluid chromatography. The electrochemical cell consisted of two electrodes and its holder, and a working and a counter electrode were fabricated from 192 carbon strings, which were composed of 400 carbon fibers of 10 μm in diameter filled into a heat‐shrinkable tube. These electrodes were placed in the center of a holder made from polyether ether ketone blocks and they were separated by polytetrafluoroethylene membrane filters. To evaluate the sensitivity of this cell, a standard solution of ferrocene was injected into the supercritical fluid chromatography system connected to the electrolytic cell. The ferrocene was eluted through a silica gel column using a mixture of a mobile phase of supercritical CO2 and a modifier of methanol containing ammonium acetate. The current peak area of ferrocene correlated to the ferrocene concentration in the range of 10–400 μmol/L ( r  = 0.999). Moreover, the limit of detection on the column estimated from a signal‐to‐noise ratio of 3 was 9.8  × 10 −13  mol.